Effects of seasonality and environmental change on an Andean damselfly Mesamphiagrion laterale (Odonata: Coenagrionidae) (2020)
Land use change, notably the conversion of natural habitats into agriculture, has strong negative effects on wild animal populations. Effects of disturbance and seasonality on demographic parameters of the damselfly Mesamphiagrion laterale Selys, 1876 were assessed to investigate how individual survival probability and over population size changed according to season and anthropogenic disturbance (agricultural habitat vs. forested habitat). For each habitat type, forest cover, area covered by vegetation, percentage of macrophytes and water physicochemical attributes were measured. Likewise, population parameters such as sex ratio, population size, life expectancy, survival and recapture rates were estimated using Cormark-Jolly-Seber (CJ-S) models. Life expectancy of the total population was lower during the rainy season, while population size and survival in males were lower in agricultural habitats during this same season. Human activities related to agriculture and livestock production in the Colombian Andes threaten the long-term viability of odonate populations through degradation of aquatic habitats. Contrary to our initially proposed hypotheses, these effects were more intense for males due to their closer association with riparian vegetation and thus greater exposure to aquatic pollutants.